1993
DOI: 10.1021/j100139a020
|View full text |Cite
|
Sign up to set email alerts
|

Partially coupled electrical model of vibrational frequency shifts in weak atom-diatomic and diatomic-diatomic complexes

Abstract: A simple model has been found to account for the blue and red shifts in the stretching transition frequencies of diatomic molecules that occur because of weak bonding to rare-gas atoms or to other diatomics. The primary . element in the model is that of electrical interaction between the interacting species. This affects transition frequencies because the electrical properties change upon vibrational excitation. A second important element is the coupling of the intramolecular stretch to the weak mode vibration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…At the long distances, the potential energy is proportional to the third power of the reciprocal distance, indicating a dominant dipole−dipole interaction. This is in agreement with Dykstra's finding that the interactions and frequency shifts in regular hydrogen bonds can be explained primarily by electrostatics and polarizability. , For each of the systems, when Y comes closer to X, the X−H length is first elongated, and then compressed. The bond elongation is a result of electrostatic interactions, charge rearrangement, and orbital interactions.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…At the long distances, the potential energy is proportional to the third power of the reciprocal distance, indicating a dominant dipole−dipole interaction. This is in agreement with Dykstra's finding that the interactions and frequency shifts in regular hydrogen bonds can be explained primarily by electrostatics and polarizability. , For each of the systems, when Y comes closer to X, the X−H length is first elongated, and then compressed. The bond elongation is a result of electrostatic interactions, charge rearrangement, and orbital interactions.…”
Section: Resultssupporting
confidence: 89%
“…Thus, we need to explore electrostatic interactions. Dykstra et al have obtained very good agreement with experiment for red-shifted X−H stretching modes in hydrogen-bonded systems by considering only the electrostatic interactions and polarizabilities of the monomers. , In an even simpler model, the interaction of a proton donor with a negative charge was used several decades ago as a conceptual framework for describing hydrogen bonds. In the spirit of this model, a negative point charge was put on the C−H axis at various distances from the carbon of F 3 CH.…”
Section: Resultsmentioning
confidence: 96%
“…To interpret the blue-shifting effects, a number of mechanisms have been proposed in recent years. Hobza and Havlas proposed a two-step mechanism in which the electron density is transferred first from the HB acceptor to a remote part of the donor followed by charge reorganization within the donor molecule. , The other mechanisms are as follows:(i) an interplay of repolarization/rehybridization of the carbon-centric orbital of the CH bond by the electric field of the acceptor group and hyperconjugative Y → σ*(CH) charge transfer at a shorter intermolecular distance of donor−acceptor molecules; (ii) contraction of the CH bond by the electric field of Y; , and (iii) interplay of electrostatic interactions and short-range overlap repulsion . Among these, the repolarization/rehybridization mechanism, which can be applied intuitively to a variety of CH···Y-type H-bonded complexes, has been found to be quite useful to interpret the bond shortening and blue shifting effects. , Apparently, attempts to utilize this model designed for 2c,2e bonds directly toward hypervalent 3c,4e-bonds in rare gas FHeH···N2 complexes were unsuccessful due to unique properties of such highly delocalized bonds .…”
Section: Introductionmentioning
confidence: 99%
“…Whatever is the sign of X-H bond deformation, it results from a balance between elongation forces and forces pushing toward contraction. A review of the literature (the basic schools of thought are included in refs ) revealed that the major effects causing the lengthening of the X-H bond are the attractive interaction between the positive H of X-H dipole and the electron-rich acceptor (lone pair or π electrons) and the hyperconjugative electron donation n (Y) → σ*(X-H), which are significant for electron-rich, highly polar, short X-H bonds. In the opposite side, the major X-H bond shortening contributors are the Pauli repulsive forces and the increased electrostatic attraction between the positive H and negative X (caused by a net gain of electron density at the X-H bond region in the presence of Y), which are significant for less polar, electron-deficient, short X-H bonds, like C-H bonds having a negative dipole moment derivative for the isolated H-bond donor molecule. , …”
Section: Introductionmentioning
confidence: 99%